Outcomes of Microwave Ablation in T1a Renal Cell Carcinomas: A Retrospective Analysis - Andrew Whittering; Anthony Franklin; Arani Halder (Journal of Clinical Interventional Radiology ISVIR, 2026)
Abstract Microwave ablation (MWA) is a suitable nonsurgical alternative for management of T1a renal cell carcinomas (RCCs). Variation exists in reported guidelines regarding the use of MWA in RCCs measuring 30 to 40 mm in size. The purpose of this retrospective study was to evaluate the overall success of MWA in managing RCCs through oncological and technical outcomes to provide insight into the management of these tumor sizes. A retrospective study of MWA for T1a RCC was undertaken at a large tertiary center between April 2018 and July 2025, identifying 42 participants. Assessment of oncological outcomes evaluated local tumor progression, out-of-field recurrence, and disease-free survival. Additionally, technical success of MWA was evaluated with focus on tumor and patient characteristics. Of the 42 participants identified, the median tumor size was 28 mm with 45% of tumors ≥ 30 mm. Technical success and safety was supported through no significant change in pre- and postablation renal function. Five participants experienced Clavien–Dindo grade III complications. Oncological outcomes were favorable with a median follow-up of 17.4 months (interquartile range 5.6–32.3 months) and 97.6% of the participants remaining free of progressive disease. The use of MWA in the management of T1a RCCs demonstrated favorable local tumor progression rates and overall survival consistent with published literature, with worsening outcomes in those tumors > 30 mm. This accompanied with high technical success further endorses MWA with consideration for surgical intervention in those tumors > 30 mm.